Analysis of the implementation of the safety and health management system (SMK3) at The Sentani Community Health Center, Jayapura Regency - Korwa, Henderjetac Carolina; Surono, Agus; Jaladara, Vena (BKM Public Health and Community Medicine, 2023)
Purpose: This research aims to analyze the implementation of the occupational safety and health management system at community health centers to determine the achievements of the implementation of occupational safety and health by looking at the indicator system from K3 policy, K3 planning, K3 implementation as well as K3 monitoring and evaluation at the Sentani Community Health Center, Jayapura Regency. Methods: This type of research uses qualitative case study methods. The subjects of this research were health workers at the Sentani Community Health Center, Jayapura Regency, with a sample size of 10 respondents. The data collection technique is a triangulation technique involving observations, in-depth interviews, and documentation studies. The tool used is a questionnaire. Results: The research shows that community health centers must fully implement an occupational safety and health management system. Based on the results of observations and interviews, it was found that the health center still needs to have a written K3 commitment and policy based on the SK—head of Pukesmas. There has been no significant risk research in determining K3 planning. The implementation of K3 at health centers has been implemented through health services, fire control and prevention, and the provision of K3 facilities and infrastructure. Monitoring and evaluation in implementing K3 still need to record and report on planning, implementation, or recording cases of work-related accidents (KAK) and work-related diseases (PAK) at health centers. Conclusion: The safety and health management system must still be fully implemented. The need to review and analyze work risks for workers and the environment and become a benchmark in making K3 policy commitments at health centers in implementing occupational safety and health management systems.